Social media report / Aida Fatin Ahmad - Ahmad, Aida Fatin (2019)
G.Louisha Korean Sling Bag offers sling bag products, providing the variety colours of sling bag that gives high satisfaction of consumer. The store is located at Seri Iskandar, Perak which it is nearby to Universiti Teknologi Mara (UiTM) Seri Iskandar and Universiti Teknologi PETRONAS. Hence, G.Louisha identifying students around Seri Iskandar who likes to be in line with the trends' fashion and those students who wish to give an affordable price present to their friends. Besides, G.Louisha korean Sling Bag also target Seri Iskandar's residents who have daughters or who want to buy the sling bags for themselves.